Bacterial load determination of poultry feed with seasonality effect in Karachi, Pakistan. - Iram, Shajeela; Khawaja, Tabinda; Mehmood ul Hassan; Khan, Muhammad Jawad; Abbas, Tanveer (International Journal of Endorsing Health Science Research, 2021)
Background: The escalating rate of food-borne diseases via poultry feeds necessitates the characterization of the pathogens to reduce the health risk factor for humans and animals. The poultry feed microbial analysis help to control food-borne illness. In addition, the knowledge about seasonal effects on microbial growth helps the manufacturers to take precautionary measures in alarming months to maintain the standard quality of poultry feed. Methodology: This study was designed to identify and enumerate bacteria and their seasonal variation. Total feed samples (n=204) were evaluated through traditional culture techniques, microscopic inspection, and biochemical properties. However, bacterial load was determined by using the total viable count. Results: As a result, five genera, including Salmonella enterica (39.05%), Escherichia coli (22.48%), Bacillus subtilis (18.34%), Staphylococcus aureus (11.24%), and Streptococcus sp (8.87%), were isolated. The proportion of occurrence of the bacterial load was lowest in December-February (64.4%) and highest in June-August (96.2%). Whereas in September-November was (87.6%) and March-May (77.5%). On the whole, the total percentage of positive samples was 82.8%. Statistical analysis revealed that (9.9×10-8 cfu/g) was the highest viable bacterial count recorded from June to August. The presence of food-borne pathogens, especially S.enterica and E.coli, is bothersome. Moreover, June to August is considered the most troubling month due to the elevated level of contamination. Conclusion: To evade microbial contamination, the microbiological security rules must be followed throughout the process of formulation and storage period, especially in sensitive hot and humid months of June to August. Also, standard inspection should be taken to control the dissemination of food-borne illness.